2020
DOI: 10.1007/s11145-020-10023-7
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal analysis of the alignment between children’s early word-level reading trajectories, teachers’ reported concerns and supports provided

Abstract: In this longitudinal study, the word-level reading trajectories of 118 children were tracked alongside teachers' reported concerns and types of support provided through Grades 1, 2 and 3. Results show a significant decline in composite scores relative to age norms over time, with children achieving significantly lower in phonemic decoding than word recognition at the subtest level. Five group trajectories were identified: children who achieved average or above average scores across all 3 years (n = 64), childr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…Our findings not only relate to the existence of LI dyslexia (Barbiero et al, 2012;Graham, White, Tancredi, Snow, & Cologon, 2020), but also to research findings that point to the challenges that educators face in identifying and shaping literacy interventions: Studies have reported that schools, school psychologists, and teachers were not always sufficiently familiar with the adequate application of the response-to-intervention framework (e.g., Kratochwill, Volpiansky, Clements, & Ball, 2007;Vujnovic et al, 2014). It has also been reported that not all children requiring more intensive literacy instruction actually receive this help (Graham et al, 2020) and that teachers' identification of reading difficulties in children does not always take place on the right information (Schmitterer & Brod, 2021). Consequently, the findings relate to the recent call of devoting more time and effort to translating research to education (Seidenberg, Cooper Borkenhagen, & Kearns, 2020) and supporting both educators' knowledge of literacy development and disorders and classroom implementation (e.g., Piasta, Connor, Fishman, & Morrison, 2009).…”
Section: Discussionmentioning
confidence: 56%
“…Our findings not only relate to the existence of LI dyslexia (Barbiero et al, 2012;Graham, White, Tancredi, Snow, & Cologon, 2020), but also to research findings that point to the challenges that educators face in identifying and shaping literacy interventions: Studies have reported that schools, school psychologists, and teachers were not always sufficiently familiar with the adequate application of the response-to-intervention framework (e.g., Kratochwill, Volpiansky, Clements, & Ball, 2007;Vujnovic et al, 2014). It has also been reported that not all children requiring more intensive literacy instruction actually receive this help (Graham et al, 2020) and that teachers' identification of reading difficulties in children does not always take place on the right information (Schmitterer & Brod, 2021). Consequently, the findings relate to the recent call of devoting more time and effort to translating research to education (Seidenberg, Cooper Borkenhagen, & Kearns, 2020) and supporting both educators' knowledge of literacy development and disorders and classroom implementation (e.g., Piasta, Connor, Fishman, & Morrison, 2009).…”
Section: Discussionmentioning
confidence: 56%
“…It is often used as an index of overall achievement" (Chall, 2000, p. 57). Put succinctly in an article from the journal Reading and Writing, deficits in reading skills prevent students from "accessing the academic school curriculum" (Graham, White, Tancredi, Snow, & Cologon, 2020, p. 1896. This is precisely what leads to an elevated drop-out rate for students with dyslexia or other reading issues-without reading skills, they simply can not engage in the tasks required of them in most classes beyond the level of primary school.…”
Section: The Prevalence Of and Consequences Of Dyslexia And Other Rea...mentioning
confidence: 99%
“…In an international level, examples of how teachers struggle with language components include: 'insufficient development concepts about language and pervasive conceptual weakness in the very skills that are needed for direct, systematic, language focused reading instructions, such as the ability to count phonemes and to identify phonic relationships' (Graham et al, 2020;McMaster et al, 2020;Moat and Lyon, 1996, p. 79). Other language components that are challenging to teachers include: manipulating speech sounds; knowledge of differencing letter-sound combination; conceptualization of functional spelling; common syllable types and division patterns; recognition of children' s difficulties with phonological, orthographic and syntactic learning (Moats and Foorman, 2003).…”
Section: Teachers' Challenges and The Peter Effectmentioning
confidence: 99%